Effects of an acute high-intensity interval training protocol on plasma viscosity - Alis, R.; Ibanez-Sania, S.; Basterra, J.; Sanchis-Gomar, F.; Romagnoli, M. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: High-intensity interval training (HIT) is an exercise model that has been seen to cause similar muscle adaptations and improvements in exercise performance to other traditional exercise models. This study aimed to examine the effects of low-volume HIT exercise on plasma viscosity (PV).